2020
DOI: 10.2147/dddt.s263787
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bone-Targeting Liposome-Encapsulated Salvianic Acid A Improves Nonunion Healing Through the Regulation of HDAC3-Mediated Endochondral Ossification</p>

Abstract: Nonunion is a major complication in fracture repair and remains a challenge in orthopaedics and trauma surgery. In this study, we aimed to evaluate the effectiveness of treatment of nonunion with a large radial defect using a bone-targeting liposomeencapsulated salvianic acid A (SAA-BTL)-incorporated collagen sponge and further elucidate whether the effects were closely related to histone deacetylase 3 (HDAC 3)-mediated endochondral ossification in nonunion healing process. Methods: Fifteen New Zealand female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The local delivery of salvianic acid A, a bone anabolic agent, along with the bone-targeting liposomes targeting bone fracture site, significantly enhanced the interaction with the bone, the retention of the liposomes in the bone, and the fracture healing in vivo. In recent study, Zhou et al reported the collagen sponge incorporated with bone-targeting liposomes formed by phosphorylated cholesterols loaded salvianic acid A for endochondral ossification [24]. The criticalsized segmental defect rabbit model was assessed to determine the effect of bone regeneration via regulation of histone deacetylase 3 (HDAC3), which is related to the formation and development of the bone extracellular matrix (ECM).…”
Section: Bone-targeting Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The local delivery of salvianic acid A, a bone anabolic agent, along with the bone-targeting liposomes targeting bone fracture site, significantly enhanced the interaction with the bone, the retention of the liposomes in the bone, and the fracture healing in vivo. In recent study, Zhou et al reported the collagen sponge incorporated with bone-targeting liposomes formed by phosphorylated cholesterols loaded salvianic acid A for endochondral ossification [24]. The criticalsized segmental defect rabbit model was assessed to determine the effect of bone regeneration via regulation of histone deacetylase 3 (HDAC3), which is related to the formation and development of the bone extracellular matrix (ECM).…”
Section: Bone-targeting Liposomesmentioning
confidence: 99%
“…Several liposomal systems for hydrophilic small molecule drug delivery have been investigated regarding controlled/sustained delivery against rapid diffusional clearance. Liposomal formulations containing salvianic acid A, as a potent inducer of osteogenesis and angiogenesis, combined with collagen scaffolds successfully stimulated bone fracture healing in mice and rabbit model [23,24].…”
Section: Hydrophilic Small Molecule Drugsmentioning
confidence: 99%
“…Cell viability were assessed after 1 and 4 days of culture using a dual staining kit for live and dead cells (Abbkine, China). 45 Stained cells were observed using an inverted fluorescence microscope (Leica, Germany). Additionally, on days 1, 4, and 7, cell proliferation was quantified using the CCK-8 assay kit (Vazyme) by measuring absorbance at 450 nm with a microplate reader (Thermo Fisher Scientific, Waltham, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Micro-CT showed significantly increased union callus formation with elevated BV and TV values in the 4th week postsurgery. Histological images showed increased bone areas in the callus, and immunofluorescence images showed increased expression of collagen II, P-HDAC3, VEGFA, osteocalcin, and RUNX2 in the callus (Zhou et al, 2020).…”
Section: Salvianolic Acidsmentioning
confidence: 96%